Pendampingan dan pelatihan cara pengambilan foto produk UMKM untuk pemasaran di media sosial - Nugraheny, Dwi; Pujiastuti, Asih; Sudaryanto, Sudaryanto; Wintolo, Hero; Agustian, Harliyus; Aryanto, Salam; Indrianingsih, Yuliani; Honggowibowo, Anton Setiawan (Institut Teknologi Dirgantara Adisutjipto, 2022)
The development of photography is very rapid and has become a very important need for human life. Many business opportunities can be created through photography, one of them is to support the marketing of a product. Product Photos are one of the factors that support so that merchandise will sold well. So it can be said that photography is a medium of visual communication in promoting products. Pengkok village is one of several villages in the Patuk Gunung Kidul sub-district which has many regional superior products produced by Micro, Small and Medium Enterprises (MSMEs). The activity of promoting superior products from the region is very important to support tourism activities and the economy of the surrounding community, especially in Patuk District, Gunung Kidul Regency. One of the activities to support promotions that can be done is taking pictures of attractive and beautiful products. Not all product photos for promotional purposes are produced from expensive and sophisticated equipment. Understanding photography techniques to take products’ photos is an important part in promoting products that attract consumers' attention. Therefore, there is a need for training in product shooting techniques using a smartphone. For this reason, to meet the needs of partners (BKAD in Patuk District) a Accompaniment/Training on product shooting techniques using Smartphones for MSME products in Pengkok village was held in the form of Community Service activities. The implementers of this service are lecturers of the Informatics Study Program, Adisutjipto Aerospace Technology Institute assisted by several students of the Informatics Study Program. This training is expected to increase the skills of the MSMEs of Pengkok Village in using smartphone cameras to take pictures of their products as marketing support, so that the resulting images/photos look better and attractive to consumers.The result of monitoring evaluation that has been done during the training is, there is 64% skill increase of the MSMEs of Pengkok Village in photography technique to take attractive product photos.